2018
DOI: 10.1016/j.case.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Clot or Not?

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Primary cardiac tumors, cardiac metastases, vegetations, thrombi, fluid-filled lesions, and artifacts form the differential diagnosis for cardiac masses [ Table 1 ]. [ 6 , 7 ] Among them atrial myxomas show the most variability in shape and consistency. Right heart thrombi are often serpiginous, highly mobile, and associated with deep vein thrombosis and pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cardiac tumors, cardiac metastases, vegetations, thrombi, fluid-filled lesions, and artifacts form the differential diagnosis for cardiac masses [ Table 1 ]. [ 6 , 7 ] Among them atrial myxomas show the most variability in shape and consistency. Right heart thrombi are often serpiginous, highly mobile, and associated with deep vein thrombosis and pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…3D echocardiography (3DE) confirmed it to be a solitary, sessile mass; however, the 3D volume data set analysis showed that the mass had a heterogeneous, granular surface texture [ Figure 2 ], few irregular calcifications in crop plane view, and random small areas of echolucency, suggestive of a tumor rather than a thrombus [ Figure 3 and Video 1 ]. [ 6 ] Surgically excised mass pointed toward it being a myxoma [ Figure 4 ].…”
Section: Case Detailsmentioning
confidence: 99%